2011
DOI: 10.1080/03079457.2011.553583
|View full text |Cite
|
Sign up to set email alerts
|

Capsid protein sequence diversity of avian nephritis virus

Abstract: The capsid gene sequences of 25 avian nephritis viruses (ANVs), collected in the UK, Germany and Belgium from the 1980s to 2008, were determined and compared with those of serotype 1 (ANV-1) and serotype 2 (ANV-2) ANV isolates. Amino acid identities as low as 51% were determined. Pairwise comparisons supported by phylogenetic analysis identified six ANVs, including ANV-1 and ANV-2, which shared<80% amino acid identities with one another, and which were selected to be representative of six groups. The ANVs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 27 publications
4
49
0
2
Order By: Relevance
“…The 3′ UTR phylogenetic tree had two major branches, with isolates from capsid groups 1, 2 and 3 clustering on one branch and isolates Table 2. Percentage identity for the capsid protein amino acid (bold) and nucleotide (italic) sequence from ANV strains identified in this study and those reported in Todd et al (2011).…”
Section: Samplementioning
confidence: 99%
See 4 more Smart Citations
“…The 3′ UTR phylogenetic tree had two major branches, with isolates from capsid groups 1, 2 and 3 clustering on one branch and isolates Table 2. Percentage identity for the capsid protein amino acid (bold) and nucleotide (italic) sequence from ANV strains identified in this study and those reported in Todd et al (2011).…”
Section: Samplementioning
confidence: 99%
“…Nucleotide identities of 86-99% were found between the polymerase gene of ANV isolates in the United States (Pantin-Jackwood, 2006). The capsid gene on the other hand is the most variable with the capsid gene of European and Asian isolates having nucleotide identities of 56-100% (Todd et al, 2011). The non-structural protein gene in Hungarian ANV isolates had nucleotide identities between 76% and 86% (Mandoki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations